2017
DOI: 10.5846/stxb201603100424
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes of diatom community structure in the Zhalong wetland and its relationship with environmental conditions

Abstract: 第 37 卷第 8 期 2017 年 4 月 生 态 学 报 ACTA ECOLOGICA SINICA Vol.37,No.8 Apr.,2017 http: / / www.ecologica.cn 基金项目:国家自然科学基金资助(31270250, 31470308) 收稿日期:2016• 03• 10; 网络出版日期:2016• 09• 19 * 通讯作者 Corresponding author.E•mail: fanyaw@ 163.com DOI: 10.5846 / stxb201603100424 代存芳,易映彤,刘妍,巴秋爽,范亚文.扎龙湿地硅藻植物群落季节变化及其对环境的响应.生态学报,2017,37(8) :2818• 2827. Dai C F, Yi Y T, Liu Y, Ba Q S, Fan Y W.Seasonal changes of diatom community structure in the Zhalong wetland and its relationship with environmental conditions.Acta Ecologica Sinica,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In terms of calculation, PMD would appear the phenomenon of zero value, and PTI needs to calculate the tolerance value of diatoms to external stress Hence, RAD emerged as the most suitable biological indicator to evaluate the water quality of Dongting Lake. Previous studies have shown that diatoms are dominant in mesotrophic lakes [37], the relative abundance of dominant diatoms are closely related to water quality in Daihai Lake [60], RAD has been selected as an important index for biological assessment of water quality in Dongting Lake during the construction of the aquatic biological integrity index [56], and TN and TP are main driving factors of seasonal succession of diatom community [13]. Of course, the suitability of RAD for water quality assessment in different regions will certainly vary, and we need to assess the accuracy of RAD based on the type and characteristics of the water body.…”
Section: Biological Assessment Of Water Quality Based On Diatom Indicesmentioning
confidence: 99%
“…In terms of calculation, PMD would appear the phenomenon of zero value, and PTI needs to calculate the tolerance value of diatoms to external stress Hence, RAD emerged as the most suitable biological indicator to evaluate the water quality of Dongting Lake. Previous studies have shown that diatoms are dominant in mesotrophic lakes [37], the relative abundance of dominant diatoms are closely related to water quality in Daihai Lake [60], RAD has been selected as an important index for biological assessment of water quality in Dongting Lake during the construction of the aquatic biological integrity index [56], and TN and TP are main driving factors of seasonal succession of diatom community [13]. Of course, the suitability of RAD for water quality assessment in different regions will certainly vary, and we need to assess the accuracy of RAD based on the type and characteristics of the water body.…”
Section: Biological Assessment Of Water Quality Based On Diatom Indicesmentioning
confidence: 99%